Low-Profile All-Textile Multiband Microstrip Circular Patch Antenna for WBAN Applications - Li, Haiyan; Du, Jinxin; Yang, Xue-Xia; Gao, Steven (IEEE antennas and wireless propagation letters, 2022)
A compact low-profile all-textile multiband antenna operating in the 2.45/5.8 GHz ISM bands, mobile WiMAX IEEE 802.16 2005 (3.3-3.4 GHz), and 5G sub-6 NR frequency band n77 (3.85-4.0 GHz) is proposed for wireless body-area network (WBAN) applications. Good broadside radiations are achieved by properly activating the inherent TM 11 , TM 21, and TM 31 modes of a circular patch antenna. An elliptical slot and a C-shaped slot are employed to tune the three modes to the desired operating frequencies. A rectangular slot is used to reduce undesirable depression in the 5.8 GHz radiation pattern. The proposed antenna is fabricated from a conductive fabric layer integrated onto a single layer of denim, making it extremely low-profile and suitable for wearable applications. It has an overall size of 60 × 60 × 1.17 mm (0.64 λ g × 0.64 λ g × 0.0125 λ g at 2.45 GHz). The measured maximum realized gains and bandwidth at the four frequencies are −0.81, −2.81, −1.16, 2.83 dBi, and 90, 190, 230, 570 MHz, respectively. Test results show that when the antenna is placed on and bent around a human arm model, the reflection coefficient has only slight influence. Since the antenna adopts full ground plane structure, the SAR values are far below the EU standard of 2 W/kg limit. With merit characteristics, the proposed design indicates a promising candidate for WBAN applications.